Sound transmission through single, double and triple glazing. Experimental evaluation - Tadeu, António J. B. (2001)
Experimental results on sound insulation of glazed openings are reported in this work. The laboratory experiments were performed placing the text specimens between two relatively small rooms. The number of glass panels, their thickness, the air gap thickness between the panels and the type of fixing frame are the variables considered. The insulation conferred by the glazed opening is characterised, identifying the localisation of the dips of insulation in the frequency domain with those related to its own natural dynamic vibration modes and those related to the natural modes of vibration of the rooms. Since the full mathematical description of the acoustic insulation conferred by glazed panels is extremely complicated, simplified theoretical models are frequently used. In this work, the experimental insulation curves obtained are compared with those predicted by the simplified analytical models. This analysis shows that the predictive models, particularly when applied to multiple glazing windows, exhibit marked differences when compared with the experimental data.